2022
DOI: 10.1038/s41597-022-01345-y
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a MS/MS database for isoquinoline alkaloids and other annonaceous metabolites

Abstract: This data descriptor reports on the upload to a public repository (GNPS) of the IQAMDB, IsoQuinoline and Annonaceous Metabolites Data Base, comprising 320 tandem mass spectra. This project originated from our in-house collection of isoquinolines. The diversity of compounds included in this database was further extended through the contribution of two additional laboratories involved in isoquinoline alkaloids research: University of Angers and University of Manaus. The generated MS/MS data were processed and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…While glaziovine is not a major constituent of sacred lotus (Menéndez-Perdomo and Facchini, 2018), several recent studies have reported its isolation from seeds of N. nucifera (Bishayee et al, 2022; Cao et al, 2022; Yu et al, 2022). In contrast, glaziovine is a major alkaloid in Ocotea glaziovii and other select species of Lauraceae and Annonaceae (Agnès et al, 2022). Our demonstration of glaziovine synthesis coupled with the inability of Nn CYP80G to act on exogenous ( R , S )-armepavine confirms that proaporphine synthesis precedes 7- O -methylation in agreement with the proposed phenol coupling mechanism (Barton and Cohen, 1957).…”
Section: Discussionmentioning
confidence: 99%
“…While glaziovine is not a major constituent of sacred lotus (Menéndez-Perdomo and Facchini, 2018), several recent studies have reported its isolation from seeds of N. nucifera (Bishayee et al, 2022; Cao et al, 2022; Yu et al, 2022). In contrast, glaziovine is a major alkaloid in Ocotea glaziovii and other select species of Lauraceae and Annonaceae (Agnès et al, 2022). Our demonstration of glaziovine synthesis coupled with the inability of Nn CYP80G to act on exogenous ( R , S )-armepavine confirms that proaporphine synthesis precedes 7- O -methylation in agreement with the proposed phenol coupling mechanism (Barton and Cohen, 1957).…”
Section: Discussionmentioning
confidence: 99%
“…Although many phytochemicals have been previously found in medicinal plants, most of them vary in the historical collections of natural product chemistry laboratories and their MS/MS spectra have not been reported. Benchmarking recent efforts leading to the monoterpene indole alkaloid database (MIADB), and isoquinoline alkaloids and other annonaceous metabolites database (IQAMDB), which are spectral libraries built with compounds from historical collections of various natural product chemistry laboratories 14 , 15 , we established an MS/MS spectral library using 223 pure phytochemicals obtained from the legacy compound library of the Natural Products Research Institute, Seoul National University (SSK Legacy Library, named after Sam Sik Kang, who compiled the library over the course of 30 years). MS/MS spectra were acquired for all ionized molecules in positive (ESI+) and negative (ESI−) ion modes, which yielded 184 positive and 152 negative ion mode spectra.…”
Section: Background and Summarymentioning
confidence: 99%
“…The sea cucumber triterpene glycosides are characterized by unique chemical structures with a conservative structural framework but significant natural diversity in some features, leading to a vast potential for structural variability. Triterpene glycosides have lanostane-and norlanostane-type aglycons, and most of them contain an 18 (20)-lactone, although aglycons with an 18 (16)-lactone or without a lactone cycle are not uncommon (Figure 1). The polycyclic nuclei of the aglycons preferably contain a 7(8)-or 9(11)-double bond and may have oxygen-containing substituents at C-12, C-17, or C-16.…”
Section: Introductionmentioning
confidence: 99%
“…The advancement of metabolomics as a powerful research tool in the field of natural products over the last two decades has promoted the development of open-access resources and databases containing experimental data and MS/MS spectra, such as Mass-Bank [14], Metlin [15], MassBank of North America (https://mona.fiehnlab.ucdavis.edu, accessed on 1 April 2023), BMDMS-NP [16], and GNPS [17]. The latter is a web-based mass spectrometry platform that combines research tools for storing, analyzing, annotating, and sharing experimental data with an open-access MS/MS database combining several dozen spectral libraries, including several specialized natural product libraries such as the Lichen DataBase (LDB) [18], the Monoterpene Indole Alkaloids DataBase (MIADB) [19], the IsoQuinoline and Annonaceous Metabolites Data Base (IQAMDB) [20], the phytochemical database Sam Sik Kang Legacy Library [21], and others. Due to the extreme complexity of the sea cucumber extracts and the enormous diversity of triterpene glycoside structures, conventional approaches in natural product research, which require the isolation of individual compounds by a combination of chromatographic techniques followed by structure elucidation by nuclear magnetic resonance (NMR) spectroscopy, mass spectrometry (MS), or other analytical techniques, are timeand labor-intensive procedures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation